The Effect of Intrinsic Motivation, Self-Efficacy, and Organizational Climate on Job Performance of Marketing Division Employees at PT.XYZ - Simowibowo, Suryana Litana; Ardi, Ardi; Berlianto, Margaretha Pink; Sunarjo, Richard Andre (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to examine the effect of intrinsic motivation (IM), self efficacy (SE), and organization climate (OC) on job performance (JP) mediated by work engagement (WE) and job satisfaction (JS). The method used is quantitative with saturated sampling, data were collected through questionnaires and analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) with 43 respondents. The results showed that intrinsic motivation, self efficacy, organization climate had a positive effect on job performance, and intrinsic motivation and self efficacy had a positive effect on work engagement. Organization climate and work engagement had a positive effect on job satisfaction. Job satisfaction and work engagement had a positive effect on job performance. The strongest mediation path analysis occurs in the relationship between intrinsic motivation and job satisfaction through work engagement, and also intrinsic motivation to job performance through work engagement which also shows a significant influence. The results of this study provide useful insights for organizations, where the main focus is directed at increasing self-efficacy and job satisfaction, while factors that have shown good performance such as intrinsic motivation, organizational climate and work engagement must still be maintained to maintain optimal organizational performance as a whole.